Analysing Gastrointestinal Helminth Infection Epidemiology and Effects in Dairy Animal Health - A Rengarajan, Girija Shankar Sahoo, Ritika Mehra (Revista Electronica de Veterinaria, 2024)
Infections with gastrointestinal helminths are a significant threat to the health of dairy animals, affecting their general well-being and production.Gastrointestinal helminth infections can happen to dairy cows, which can have adverse effects on their public health, reduced milk production, and weight loss. There needs to be more knowledge about the frequency, distribution, and results of helminth infections on dairy animal populations despite the dairy industry’s importance to the region’s agriculture.The aim of this study is to examine the epidemiology of gastrointestinal helminth infections in dairy animals and evaluate their implications on overall health. Through the identification of common helminth species, comprehension of seasonal fluctuations, and assessment of the effects on various dairy animals, our objective is to offer significant perspectives for focused intervention and management strategies.On dairy farms in a predetermined region, 183 animalslike 90 cows, 15 buffaloes, 28 sheep, and 50 goats were used in a cross-sectionedresearch. To identify the percentage of nematodes, protozoa, trematodes, and cestodes, they gathered and examined samples. Seasonal data collection was performed to monitor fluctuations in rates of infection.The outcomes were examined using statistical approach. The nematodes are the most prevalent gastrointestinal helminth infection in domestic ruminants, with a modest the rate globally. To preserve the welfare of the area herd and dairy production, they emphasized the need for preventative measures and cures.